The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1086/302441
|View full text |Cite
|
Sign up to set email alerts
|

Highly Skewed X-Chromosome Inactivation Is Associated with Idiopathic Recurrent Spontaneous Abortion

Abstract: Mutations of UFD1L Are Not Responsible for the Majority of Cases of DiGeorge Syndrome/ Velocardiofacial Syndrome without Deletions within Chromosome 22q11 To the Editor: Deletions of chromosome 22q11 are associated with a wide spectrum of congenital malformation, encompassed by the acronym "CATCH22" (cardiac defects, abnormal facies, thymic hypoplasia, cleft palate, and hypocalcemia on chromosome 22), including velocardiofacial syndrome (VCFS; MIM 192430), DiGeorge syndrome (DGS; MIM 188400), and conotruncal-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 95 publications
2
65
3
1
Order By: Relevance
“…It is possible that different tissues in the body may have different X-inactivation patterns, for example, the brain may have a more random pattern of X-inactivation compared with blood. Previous studies in our laboratory have shown excellent concordance in X-inactivation patterns of 45 women between two types of tissues, peripheral blood cells (mesoderm) and oral mucosal cells (endoderm), 39 suggesting that tissue-specific differences in X-inactivation patterns may be rare. A limited study of X-inactivation patterns in brain tissue have shown random X-inactivation patterns for all patients.…”
Section: The Patients Were Then Divided Into Five Mutation Groups: Mbmentioning
confidence: 72%
See 1 more Smart Citation
“…It is possible that different tissues in the body may have different X-inactivation patterns, for example, the brain may have a more random pattern of X-inactivation compared with blood. Previous studies in our laboratory have shown excellent concordance in X-inactivation patterns of 45 women between two types of tissues, peripheral blood cells (mesoderm) and oral mucosal cells (endoderm), 39 suggesting that tissue-specific differences in X-inactivation patterns may be rare. A limited study of X-inactivation patterns in brain tissue have shown random X-inactivation patterns for all patients.…”
Section: The Patients Were Then Divided Into Five Mutation Groups: Mbmentioning
confidence: 72%
“…In these women, the X-linked mutant locus leading to skewed X-inactivation must be on the same chromosome (in cis) with the mutant MeCP2 gene, leading to preferential inactivation of the X chromosome with the MeCP2 mutation. We have recently shown in other studies that many females showing highly skewed X-inactivation are carriers of X-linked recessive lethal disorders, which result in death or a growth disadvantage of cells having the abnormal X active 39,40 (Lanasa et al, in press). Similarly, we have found patterns of skewed X-inactivation in clinically manifesting carriers of X-linked recessive traits such as Duchenne dystrophy.…”
Section: The Patients Were Then Divided Into Five Mutation Groups: Mbmentioning
confidence: 99%
“…Preferential XCI is an infrequent event in humans, which can be associated with conditions such as extensive X chromosome structural rearrangements, X-linked lethal traits and reduction of the number of embryonic precursor cells in the inner mass at the time of XCI commitment. 4,5 In extra-embryonic tissues of marsupials and mice, the X P is always inactivated. 3 In humans, conflicting data have been reported; of four recent studies, using the methylation assay of androgen receptor (AR), one reported X P preferential inactivation, 6 and three showed both random and preferential XCI.…”
Section: Introductionmentioning
confidence: 99%
“…[18], 80% [19], and 90% have been employed [20]. In the current study, skewing of the X chromosome was defined if the percentage activity of a single allele was ≥ 80% in heterozygous samples [19].…”
Section: Hormone Assaysmentioning
confidence: 99%